The Customer Satisfaction at Hotel ABC BEKASI: The Role of Service Quality, Corporate Image, and Location - Diyan Putranto; Sri Marini; Adi Sopyan; Anindita Gayatri; Barliani Dewi Setyawati; Banundoyo Albertus (PT FORMOSA CENDEKIA GLOBAL, 2023)
The study explores the impact of service quality, corporate image, and location on patron satisfaction at the ABC Hotel in Bekasi City. Results reveal a significant link between service quality and customer happiness, denoted by a substantial 0.550 coefficient of effect, supported by a p-value below 0.05. Similarly, corporate image wields influence, showing a p-value of 0.003, signifying its importance. Location also plays a role, with a 0.522 coefficient of effect on consumer satisfaction, backed by a p-value less than 0.05. These findings stem from a quantitative approach employing regression analysis, ensuring the accuracy of the data and statistical methods applied. Notably, service quality characteristics exhibit a strong impact on customer satisfaction, with a 0.550 coefficient of effect, while corporate image attributes influence it by 0.293 with a p-value of 0.003.